Re-phrasing the question: A simple tool for evaluation of adherence to therapy in patients with inflammatory bowel disease. Issue 6 (October 2017) - Engel, T; Ungar, B; Ben-Haim, G; Levhar, N; Eliakim, R; Ben-Horin, S
Background: Non-adherence to medication in patients with inflammatory bowel disease (IBD) is a challenging problem which is often overlooked or under-estimated by the physician or denied by the patient. We aimed to examine if re-phrasing the wording of the question used by the physician could help in revealing more patients who are non-adherent, and for whom appropriate counseling may be instituted. Methods: A cross-sectional questionnaire-based study of IBD patients treated in a tertiary center was conducted. Patients received a questionnaire detailing their treatments and disease course, as well as their perceptions about disease. Two forms of questions about adherence were deliberately placed in two separate parts of the questionnaire: One was 'are you taking your medications regularly as prescribed?' (Standard question), and the second, more emphatic question, was 'how often does it happen that you miss a drug dosing?' (Re-phrased question). The rate of non-adherence disclosed by each of these questions was compared. Sensitivity, specificity and predicative values were computed for each question against the conventional definition of non-adherence as taking of less than 80% of prescribed medication doses disclosed by any of the methods. Predictors of non-compliance and of denying non-compliance were also explored. Results: Overall, 165 patients were included (49% female, mean age 33.7 ± 12.7 SD, median age 30 years, 29.6% with ulcerative colitis, 62.4% with Crohn's disease). Upon questioning, 50 (30.3%) of the patients admitted to non-adherence in the last month when asked by the emphatic re-phrased question format, compared with only 10 patients (6%) reporting non-adherence when asked directly by the standard question (OR 7.4, 95%CI 3.6–15.2, p  < 0.001). Thus, a 'Do you take your medicine regularly' question format disclosed only 20% of genuinely non-compliant patients and had 16% sensitivity and 98.2% specificity for revealing non-adherence (PPV 80%, NPV 72.9%) compared with the reference re-phrased question. The leading cause for non-adherence was skepticism about drug efficacy or safety (20.5%), followed by vacation or weekend (15%), problems with prescription or pharmacy (13.5%) and forgetfulness (10%). No single demographic or clinical factor correlated with non-adherence. The only factor which correlated with higher probability for non-adherence was biological and combination treatment. Conclusion: Non-compliance with treatment is much more common than patients admit. Asking patients how often does it happen that they miss a drug dosing is a simple, practical tool which performs significantly better in disclosing non-adherence compared with asking patients if they take their medication as they should.